Sustainable Development Principles for Engineering Educator - J. C. Quadrado; M. F. Galikhanov; K. K. Zaitseva (Высшее образование в России)
This paper focuses on the justification and incorporation of sustainable development course into the certified training of engineering educators. Under the ERASMUS+ Project ENTER, a consortium was set up to build the capacity of engineering HEIs by strengthening engineering educators’ preparation by an innovative kind of engineering pedagogy. One of the project tasks is to create a novel multicultural and international approach for formal post-graduate professional and pedagogical education of engineering educators. After a thorough educational market analysis, study of HEIs requirements and educators’ needs, a formal training program was designed. One of the core courses of that program is the course on Sustainable Development. The main aim of this course is to help educators to develop a strategy how to integrate sustainable development principles into engineering education at large.